PENGARUH SALES GROWTH, EFEKTIFITAS KOMISARIS INDEPENDEN DAN KINERJA LINGKUNGAN TERHADAP KINERJA KEUANGAN PERUSAHAAN - Muhammad Fahmi Maulana (2022)
This research aims to examine the effect of sales growth, independent commissioners and environmental performance on the company's financial performance. The population that is the object of research is manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2017 - 2020 period, totaling 193 companies. In determining the sample, a purposive sampling technique was used with a total of 64 companies selected as samples. This research uses quantitative analysis techniques as an analytical method. The hypothesis was tested using Panel Data Regression Analysis with a significance level of 5 percent and the profitability ratio of Net Profit Margin as a measurement of the dependent variable. The results obtained from this test are: 1) Sales growth has a significant positive effect on the company's financial performance 2) Independent commissioners have no significant effect on the company's financial performance 3) Environmental performance has no significant effect on the company's financial performance.